Descemet membrane detachment post- phacoemulsification - Muhammad Najmi K,; Logeswary K,; Rona Asnida Nasaruddin,; Wan Haslina WAH,; Umi Kalthum MN,; Aida Zairani Mohd Zahidin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
We report the case series of phacoemulsification-related Descemet membrane detachment (DMD) encountered at a tertiary hospital in Kuala Lumpur. Case 1 was an iatrogenic DMD which was detected intraoperatively and managed early with good outcome. Case 2 and case 3 described unusual presentation of DMD which was initially undiagnosed. This report highlights the use of anterior segment optical coherence tomography (ASOCT) in detecting and confirming the correct diagnosis for DMD. With the aid of an experienced corneal specialist, the higher threshold for suspicious occurrence of DMD was confirmed using ASOCT. Treatment was tailored accordingly, with successful clearance of corneal oedema and visual recovery. This case series highlighted the importance of proper operative documentation and high threshold for suspicion for DMD in focal corneal oedema following an otherwise uneventful cataract surgery. It is concluded that ASOCT is an excellent tool to confirm diagnosis of DMD and success of treatment.